BLUNT ABDOMINAL TRAUAMA AND PA"t"rkRN OF VISCERAL INJURIES - Masood Ahmed Qureshi’,MuhammadSharif Awan2, Imtiaz Ali Langah3, Mushtaque Ahmed Abbasi4, Masoom Ali Shah5, Farkhana Yasmin6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2019)
OBJECTIVES: The visceral injuries, resulted from blunt abdominal trauma, their pattern, morbidity and mortality at Peoples University of Medical & Health Sciences for Women Nawabshah STUDY DESIGN: Prospective Observational study. PLACE AND DURATION OF STUDY:This study was conducted at Surgical Units of Peoples University of Medical and Health Sciences (PUMHS) for women and Jinnah Medical Center Nawabshah from January 2016 to December 2018. PATIENTS AND METHODS: About 66 patients were included in this study and admitted through ER (Emergecy Room) of all three surgical units of PUMHS Nawabshah. After resuccitation and necessary investigations like base line , ultrasound and CT Scan etc the pateints were explored and the injuries were noted, The data was recorded on a proforma, theb entered on MS Excel and analyzed by SPSS version 21. Demographic data, Frequencies and Percentages were calculated for presentation of qualitative variables like sex, presenting complaints, signs and symptoms and the quantitative variables like age presented by mean + standard deviation. RESULTS: 26 of 66 patients did not need surgery treated on medicines and close observation. In 40 patients laparotomy was performed. Mean age was 32.5 years Road TraWic Accident (RTA) was the most common mode of injury in Blunt Abdominal Trauma (BAT) noted in about 35 patients (53.03%). Male to female ratio was 4.2:1. Most of the patients presented in BAT as pain in abdomen 56 (84.849c), tender abdomen 40 (60.609c) Distension 36 (54.549c), Shock 18 (27.279a), Vomiting 20 (30.309a) and absent or sluggish gut sounds 50 (75.759c). Hepatic trauma 20 (30.309c) little bit more than the splenic injuryl8 (27.279c) and intestinal injury the third number 14 (21.219c). Postoperatively surgical site infection, respiratory tract infection and sepsis occurred in about 24 patients and mortality was about 6 (11%) cases. CONCLUSION: Pattern of visceral injuries results from blunt trauma abdomen is more in solid visceras rather than intestine, Road traffic Accident is the common source of trauam hence preventive measures should be adopted like seat belt, careful driving and to follow the traffic rules.